Selected studies in donesian economics on Indonesia; Concept of dualism in theory and policy - "Scholars, Dutch" (Amsterdam, 1961)
The primary object of this paper is to present a methodological study which is concerned with how to clarify and evaluate the characteristics of that social and economic structure which is called (3z(Bdual economy(3y (Bin today's developing countries. It attempts a critical review of the concepts developed by J. H. Boeke, J. van Gelderen, J. S. Furnivall, H. Frankel, H. Myint, G. Myrdal and C. Geertz, among those who have taken the view of (3z(Bsocial dualism.(3y (BIt concludes that the concept of a dual economy should be perceived in terms of (3z(Bcolonial social dualism(3y (Bas a system; and that it is solely from this point of view that the nature and direction of economic development in the context of economic nationalism in developing countries can adequately be explained.s
Keywords: Economics